The Development of Learning Media Based on Islamic Comics in Natural Sciences Force and Motion Material - Irfa'i Alfian Mubaidilla; Ziana Dhurrotul Ainiyah (Madrosatuna: Journal of Islamic Elementary School, 2022)
This research and development aims to increase the effectiveness of learning in class IV SD Muhammadiyah 9 Malang. The development of Islamic comic-based learning media aims to (1) produce learning media products by describing the media development process, (2) describe the level of feasibility of learning media, and (3) describe the level of effectiveness of learning media in the science material subject force and motion of Muhammadiyah 9 "Panglima Sudirman" Malang fourth grade elementary school students.This study refers to the Borg and Gall research model by adopting six main steps, namely: 1) needs analysis, 2) media development, 3) media testing, 4) media revision, 5) field testing, and 6) implementation. Data analysis used the Linkert scale for media eligibility data and SPSS 16.0 for Windows for media effectiveness data. Islamic comic-based learning media has been declared valid by experts. Attendance from stage I test material experts was 79%, stage II test material experts were 100%, linguists were 100%, media design experts were 100%, and learning practitioners or class teachers were 100%. The application of learning media was carried out in 3 stages, namely small group tests with 4 students, medium groups with 16 students, and large groups with 19 students in the control class and 19 students in the experimental class. Islamic comic-based learning media effectively improves student learning outcomes in class IV Al Batani as an experimental class, which is 90.56 with an increase in the average value of 21.18%, starting from 74.73 to 90.56.